Needlescopic versus conventional laparoscopic surgery for colorectal cancer ~a comparative study~ - Masashi Tsuruta; Hirotoshi Hasegawa; Koji Okabayashi; Kohei Shigeta; Takashi Ishida; Masashi Yahagi; Yoshiyuki Ishii; Yuko Kitagawa (Journal of the Anus, Rectum and Colon, 2017)
Objectives: This study set out to determine whether Needlescopic surgery (NS) produces comparable surgical outcomes for patients with colorectal cancer (CRC) compared to conventional multi-port laparoscopic surgery (MPS). Methods: We used the five-port method with a 3.5 cm umbilical incision for extraction and reconstruction during MPS for CRC. One or two 5 mm ports were exchanged for needle forceps and all surgical procedures were as for previous MPS since July 2012. We investigated the short-term outcomes of 138 consecutive patients who underwent curative resection of CRC by NS (July 2012-August 2014) and 130 consecutive patients with CRC treated with MPS during a previous period (January 2010-June 2012). Results: Operative time in the NS group was comparable to that of MPS (p=0.467); the NS group had significantly less estimated blood loss (p=0.002) and a shorter postoperative hospital stay (p<0.001). The mean number of dissected lymph nodes was 27 in both groups (p=0.730). No mortality occurred in either group, and similar morbidity rates were observed (p=0.454). Conclusions: NS using Endo Relief needle forceps is a safe and feasible option compared to conventional MPS for CRC.